Effects of Cardiac Rehabilitation on Sexual Dysfunction of Post Myocardial Infarction Patients - Jamshid Najafian (University of Social Welfare and Rehabilitation Sciences, 2001)
Objective: The common sexual complains in patients with coronary heart disease and post myocardial infarction are decrease in libido, impotence, and premature or delay ejaculation. Cardiac rehabilitation could decrease many of the psychological features of myocardial infarction and also increase exercise capacity of patients. Rehabilitation may also improve sexual disturbances in these patients directly or indirectly. This study is a clinical trial that evaluate the effect of rehabilitation on sexual problem of post MI patients. Materials & Methods: 60 patients took part in this study. All of them were men aged between 35 and 65. All patients had myocardial infarction one month ago. 30 patients were referred for cardiac rehabilitation (Case), and 30 people were patients who were not recommended to take part in rehabilitation because their physician did not believe on rehabilitation. Questioner for anxiety, depression, impotency, libido and premature ejaculation were evaluated by before and after study period. The cardiac rehabilitation composed of 24 sessions. Each session consisted of one hour of aerobic exercise (10 min warm up, 10 min cool down and 40 min isotonic exercise). Results: After cardiac rehabilitation the scores for anxiety, depression, premature ejaculation and impotency were decreased and the scores of libido were increased. In both case and control groups, the changes were significant by paired t test P<0.05. The differences between case and control were significant for depression, libido and impotency by independent t test. Conclusion: Cardiac rehabilitation could improve sexual problems in post myocardial infarction patients directly and indirectly by effect on psychological characteristics.